Assessing disparities in cancer resources distribution in Mexico - Elysse Bautista-Gonzalez; Andrés Quintero Leyra; Teresa Verenice Munoz Rocha; Heber Tomás Reyes-García; Enrique Soto-Perez-de-Celis; Alejandra Palafox Parrilla; Alejandro Mohar Betancourt; Richard Sullivan (BMC Health Services Research)
Abstract Background Given the rising cancer burden, the capacity of Mexico’s healthcare system to effectively address cancer care through its current available infrastructure becomes increasingly critical. Limited availability of diagnostic and therapeutic infrastructure leads to delays in diagnosis and treatment. Countries like Mexico, should undertake comprehensive assessments of infrastructure and human resources available for cancer, including its quantification and geolocation, to understand the service gaps. This study seeks to map oncological infrastructure in Mexico in five types of cancer: breast, lung, prostate, colon, and cervix. Methods Through a realist evaluation of publicly available databases from the High Specialty Medical Equipment National Inventory and the General Direction of Health Information, a comprehensive identification and classification of cancer resources was conducted with the intended outcome to map cancer care infrastructure in Mexico. Guided by the literature, resources necessary for diagnosis and treatment were selected by an expert consensus. Thereafter, facilities were classified by service scope into either diagnostic or diagnostic and therapeutic, and by infrastructure level into core or enhanced and then mapped geographically. Results From N = 14,133 unique healthcare facilities that deliver any type of healthcare, only 5% provided cancer care. Cancer-specific infrastructure that can provide diagnosis and treatment at the national level included N = 10 brachytherapy, N = 11 cobalt-60, N = 21 linear particle accelerators and N = 188 operating rooms. Five issues were found: (1) low availability of core therapeutic infrastructure across all cancer types; (2) regional and national centralization of available therapeutic infrastructure for all cancer types, whilst no centralization found in diagnostic resources; (3) inconsistent allocation of resources in densely populated areas; (4) infrastructure disparities per cancer type i.e., Lung, prostate, and breast cancer require significant investments in diagnostic infrastructure compared to cervical and colon cancer, and (5) lack of precise and updated infrastructure data from the public health system that requires either new codes or subcodes. Conclusions Addressing disparities in cancer resources distribution in Mexico is a dual imperative—ensuring equity while seizing an opportunity to fortify the overall health system for people without social security coverage.